“Lone” atrial fibrillation is associated with impaired left ventricular energetics that persist despite successful catheter ablation - Wijesurendra, R; Liu, A; Eichhorn, C; Ariga, R; Levelt, E; Clarke, W; Rodgers, C; Karamitsos, T; Bashir, Y; Ginks, M; Rajappan, K; Betts, T; et al. (American Heart Association, 2016)
Background “Lone” atrial fibrillation (AF) may reflect a subclinical cardiomyopathy that persists after sinus rhythm (SR) restoration, providing a substrate for AF recurrence. To test this hypothesis, we investigated the effect of restoring SR by catheter ablation on left ventricular (LV) function and energetics in patients with AF but no significant comorbidities. Methods Fifty-three patients with symptomatic paroxysmal or persistent AF and without significant valvular disease, uncontrolled hypertension, coronary artery disease, uncontrolled thyroid disease, systemic inflammatory disease, or diabetes (i.e. “lone” AF) undergoing ablation and 25 matched controls in SR were investigated. Magnetic resonance imaging quantified LV ejection fraction (LVEF), peak systolic circumferential strain (PSCS), and left atrial volumes and function, while Phosphorus-31 MR spectroscopy evaluated ventricular energetics (ratio of phosphocreatine-to-adenosine triphosphate [PCr/ATP]). AF burden was determined pre- and post-ablation by 7-day Holter monitoring; intermittent ECG event monitoring was also undertaken after ablation to investigate for asymptomatic AF recurrence. Results Before ablation, LV function and energetics were both significantly impaired in patients compared to controls (respectively: LVEF 61% [IQR 52–65%] versus 71% [IQR 69–73%], p<0.001; PSCS -15% [IQR -11 to -18%] versus -18% [-17 to -19%], p=0.002; PCr/ATP 1.81±0.35 versus 2.05±0.29, p=0.004). As expected, patients also had dilated and impaired left atria compared to controls (all p<0.001). Early after ablation (1 to 4 days), LVEF and PSCS improved in patients recovering SR from AF (respectively: LVEF +7.0±10%, p=0.005; PSCS -3.5±4.3%, p=0.001) but were unchanged in those in SR during both assessments (both p=ns). At 6-9 months post-ablation, AF burden reduced significantly (from 54% [IQR 1.5%-100%] to 0% [IQR 0%-0.1%], p<0.001). However, LVEF and PSCS did not improve further (both p=ns) and remained lower than in controls (p<0.001 and p=0.003, respectively). Similarly, there was no significant improvement in atrial function from pre-ablation (p=ns), and this also remained lower than in controls (p<0.001). PCr/ATP was unaffected by heart rhythm during assessment and AF burden before ablation (both p=ns). It was unchanged post-ablation (p=0.57), remaining lower than in controls irrespective of both recovery of SR and freedom from recurrent AF (p=0.006 and p=0.002, respectively). Conclusions “Lone” AF patients have impaired myocardial energetics and subtle LV dysfunction, which do not normalise after ablation. These findings suggest that AF may be the consequence (rather than the cause) of an occult cardiomyopathy, which persists despite a significant reduction in AF burden following ablation.